Penerapan Understanding By Design dalam Perencanaan Pembelajaran Penegakkan dan Perlindungan Hukum di Indonesia - Sari; Riski Anggita; Sri Suneki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Understanding by Design (UbD) is a learning approach in education that prioritizes the learning objectives themselves. Based on observations at SMA Negeri 8 Semarang, not all of the teachers implemented the learning methods recommended in the Independent Curriculum, where lectures and the application of UbD were still the solution. This research aims to present information on how to implement the UbD framework. This research is important for teachers in helping to develop learning plans that are in accordance with the latest curriculum, namely the Merdeka Curriculum. The first stage is determining learning objectives which determine a total of 8 objectives which are guided by Core Competencies, Basic Competencies and Competency Achievement Indicators. The second stage is determining the evaluation which includes an assessment and contains evaluation questions to achieve the stated goals. The third stage in preparing a learning plan based on UbD regarding law protection and enforcement in Indonesia is the learning step. After the learning plan is prepared, it is then prepared for a review sheet as an inspection and assessment instrument for the reviewer